The Experience in Nicaragua: Childhood Leukemia in Low Income Countries—The Main Cause of Late Diagnosis May Be "Medical Delay". (12th February 2012) - De Angelis, C.; Pacheco, C.; Lucchini, G.; Arguello, M.; Conter, V.; Flores, A.; Biondi, A.; Masera, G.; Baez, F.
Abstract : Background . The event-free survival for pediatric leukemia in low-income Countries is much lower than in high-income countries. Late diagnosis, which is regarded as a contributing factor, may be due to "parental" or "medical" delay. Procedures . The present study analyses determinants of lag time from first symptoms to diagnosis of leukemia, comparing pediatric (0–16 years old) patients in two referral centers, one in Nicaragua and one in Italy. An observational retrospective study was conducted to assess factors influencing the time to diagnosis. Results . 81 charts of children diagnosed with acute myeloid leukemia or lymphoblastic leukemia were analyzed from each centre. Median lag time to diagnosis was higher in Nicaragua than in Italy (29 versus 14 days, P < 0.001 ) and it was mainly due to "physician delay" (16.5 versus 7 days, P < 0.001 ), whereas "patient delay" from symptoms to first medical assessment was similar in the two centers (7 versus 5 days, P = 0.27 ). Moreover, median lag time from symptoms to diagnosis was decreased in Nicaraguan districts were a specific training program upon childhood oncological diseases was carried out (20.5 versus 40 days, P = 0.0019 ). Conclusions . Our study shows that delay in diagnosis of childhood leukemia is mainly associated with "physician delay" and it may be overcome by programs of continuous medical education.